Sustainable Livestock Management for Poverty Alleviation and Food Security - Hooft, Katrien E. van’t (CABI, 2014)
This practical learning guide is about supporting livestock within the smallholder mixed farming systems around the world. It provides practical ways to understand and improve smallholder animal husbandry under a variety of agricultural and ecological conditions – based on the Endogenous Livestock Development (ELD) approach. Agriculture and culture are two systems that must work together for the benefit of men and women in rural and urban communities. The title of this book could be livestock in a fast changing world. An estimated 70% of the world’s rural as well as urban poor rely on livestock for their livelihoods. Two-thirds of all livestock are found in developing countries, while even developed countries find rural and urban poor livestock keepers with similar needs. Most smallholder farmers under these circumstances practise multi-purpose, low-input methods of livestock keeping. All livestock and crop farmers today – especially those living in marginalized areas – are faced with rapidly changing socio-economic and ecological conditions. These include unexpected and recurring droughts, floods, extremes of temperature and other effects of climate change. Social changes overlie these environmental impacts because of out- migration of youth, larger production units owned by larger corporate units displacing the small farmer, land grabbing; all of this while there is a trend for improved markets for live- stock products and by-products because of growing urban populations. The writers of this training manual acknowledge that improving animal health and husbandry by rural and urban smallholder livestock keepers is not easily accomplished. All too often the multiple needs of the farmers are often not understood by donors and sup- port providers, traditional practices are too often ignored and the right approaches to train- ing are not taken. Farmers often return from training with new knowledge that does not fit their reality, or do not have the means to put the practices in place. It is commonly found that short courses and demonstration farms are not the total answer and often do not result in lasting change in animal health and production.